THE JURIDICAL REVIEW OF FREELANCE WORKERS BASED ON THE PRINCIPLES OF JUSTICE - Sundalangi, Yofriko (Tadulako Law Review, 2018)
This research aimed to investigate and obtain a clear picture about the status and the legal relationship of the freelance workers and the implementation of the manpower act to protect the freelance workers based on the justice principles. To expect that this research would be benefit for the readers in providing inputs or information about the status and the legal relationship with the freelance workers and the implementation of the manpower act to protect the freelance workers. The research used the normative empirical approach. The research population comprised the freelance workers, employers, and the data from the Department of Manpower and from the Social Security Administration Agency For Manpower in Makassar City. The samples were chosen using the Snowball Sampling Method and the descriptive analysis technique. The research results indicated that there had been many legal smuggling actions done by the enterpreneurs in their working relationship due to the absence of the clear regulations about the freelance workers. The enterpreneurs had not entirely fulfilled their responsibilities to the freelance workers, such as the wages of the workers had not been in accordance with MSEs, BPJS, Employment, Occupational Safety and Health. On the other hand, the freelance workers themselves were not yet aware of their rights and obligations because of the absence of the clear legal relationship set forth in the employment agreement and the lack of knowlegde. In fact, the employers should have implemented the provisions of the Employment Law which had been applied in accordance with the moral and legal responsibility.